Phase Separation in Anaerobic Digestion: A Potential for Easier Process Combination? - Janesch, Eike; Pereira, Joana; Neubauer, Peter; Junne, Stefan (Frontiers in Chemical Engineering, 2021)
The flexibilization of bioenergy production has the potential to counteract partly other fluctuating renewable energy sources (such as wind and solar power). As a predictable and controllable energy source, anaerobic digestion (AD) can offer on-demand energy supply through biogas production. Separation of the stages in anaerobic digestion represents a promising strategy for the flexibilization of the fermentative part of biogas production. Segregation in two reactor systems facilitates monitoring and control of the provision of educts to the second methanogenic stage, thus controlling biogas production. The first hydrolytic acidogenic stage can be operated so that different waste- and side streams e.g., from agriculture, can be converted. Two-stage operation has proven to reach similar or even higher methane yields and biogas purities than single-stage operation in many different fields of application. It furthermore allows methanation of green hydrogen and an easier combination of material and energy use of many biogenic raw and residual biomass sources. A lot of research has been conducted in recent years regarding the process phase separation in multi-stage AD operation, nevertheless, it is not often applied in practice yet. Several hurdles still exist for scale up and process control for a stable operation. This review aims to summarize the state-of-the-art, new perspectives for coupling processes and system integration of AD and challenges that currently still exist at two-stage AD. Thereby, cell physiological and engineering aspects as well as basic economic feasibility aspects are considered.